HUBUNGAN MOVEMENT BEHAVIOUR DENGAN HEALTH-RELATED QUALITY OF LIFE REMAJA SELAMA PANDEMI COVID-19 (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
Health is a state of complete physical, mental and social well-being and not merely the absence of disease or disability. Various studies have shown that adequate levels of physical activity, limited screen time, and adequate sleep is positively related to indicators of physical and mental well-being in children and adolescents. This accumulation of evidence eventually led to the publishing of the Canadian 24-h Movement Guidelines for Children and Youth. However, the COVID-19 pandemic has resulted in the implementation of policies that affect movement behaviour which is highly affecting HRQoL (health-related quality of life). The purpose of this study is to determine the relationship between movement behaviour and HRQoL during the COVID-19 pandemic. This research is an analytical study with a cross-sectional design with a sample size of 160 respondents. Sampling was done by distributing questionnaires. The result shows that Most students (129, 80.6%) do physical activity less than 1680 MET-minute/week, 70 (43.8%) students sleep for 6-8 hours, 45 (28.1%) students do sedentary activities for 5-6 hours, and 120 (75%) students don’t meet all the recommendations of the Movement Guidelines. 145 (90.6%) students have good physical HRQoL, while the other 15 (9.4%) are bad. Students’ HRQoL mental components are good on 90 (56.3%) students while 70 (43.7%) others are bad. Statistical analysis shows a significant relationship between sleep duration and the mental components summary of HRQoL (r=0.189 p= 0.008) and a significant relationship observed between meeting the recommendations of the Movement Guidelines and mental components summary of HRQoL (r= 0.170 p=0.016). Keywords: Movement Behaviour; Health-Related Quality of Life; High School Students; COVID-19 Pandemic AbstrakKesehatan adalah suatu keadaan sejahtera yang meliputi fisik, mental, dan sosial yang tidak hanya bebas dari penyakit atau kecacatan. Berbagai penelitian telah menunjukkan bahwa tingkat aktivitas fisik yang cukup, screen time yang terbatas, dan tidur yang cukup secara positif terkait dengan indikator kesejahteraan fisik dan mental anak-anak dan remaja. Akumulasi bukti ini mengarah pada dikeluarkannya Canadian 24-h Movement Guidelines for Children and Youth. Namun adanya pandemi COVID-19 mengakibatkan diterapkannya berbagai kebijakan yang mengakibatkan terpengaruhnya movement behaviour yang sangat berhubungan dengan health-related quality of life. Tujuan penelitian ini adalah untuk mengetahui hubungan movement behaviour terhadap HRQoL (health-related quality of life) siswa selama pandemi COVID-19. Penelitian ini merupakan penelitian analitik dengan desain potong-lintang dengan besar sampel 160 responden. Pengambilan sampel dilakukan dengan penyebaran kuesioner. Hasil penelitian menunjukkan karakteristik movement behaviour yaitu sebagian besar siswa (129, 80,6%) melakukan aktivitas fisik kurang dari 1680 MET-menit/minggu, 70 (43,8%) siswa tidur selama 6-8 jam, 45 (28,1%) siswa melakukan kegiatan sedentary selama 5-6 jam, dan 120 (75%) siswa tidak memenuhi semua rekomendasi Movement Behaviour Guidelines. HRQoL fisik siswa yaitu 145 (90,6%) siswa baik, sedangkan 15 (9,4%) lainnya buruk. HRQoL komponen mental siswa yaitu 90 (56,3%) siswa baik sedangkan 70 (43,7%) lainnya buruk. Uji statistik menunjukkan terdapat hubungan bermakna antara durasi tidur dengan ringkasan komponen mental HRQoL (r=0,189 p= 0,008) dan hubungan bermakna antara memenuhi rekomendasi Canadian Movement Guidelines dengan ringkasan komponen mental HRQoL (r=0,170 p=0,016).